Reducing the Vulnerability of Azerbaijan's Agricultural Systems to Climate Change : Impact Assessment and Adaptation Options - Ahouissoussi, Nicolas (Washington, DC: World Bank, 2014)
In countries such as Azerbaijan, the risks of climate change for the agricultural sector are a particularly immediate and important problem because the majority of the rural population depends either directly or indirectly on agriculture for their livelihoods. The need to adapt to climate change in all sectors is now on the agenda of the countries and development partners. International efforts to limit greenhouse gases and to mitigate climate change now and in the future will not be sufficient to prevent the harmful effects of temperature increases, changes in precipitation, and increased frequency and severity of extreme weather events. In response to these challenges, the World Bank and the government of Azerbaijan embarked on a joint study to identify and prioritize options for climate change adaptation of the agricultural sector. The study provides a framework for evaluating alternatives for investment in adaptation for the Azerbaijani government, potentially assisted by the donor community, and for the private agricultural sector. The framework has two critical components: (i) rigorous quantitative assessments, and (ii) structured discussion with local experts and farmers. The study recommends specific actions for policy makers ranked according to the results of the quantitative and qualitative analyses.